2023
DOI: 10.5935/2965-2774.20230009-en
|View full text |Cite
|
Sign up to set email alerts
|

Extubation failure and the use of noninvasive ventilation during the weaning process in critically ill COVID-19 patients

Viviane Martins Corrêa Boniatti,
Chaiane Ribeiro Pereira,
Gabriela Machado Costa
et al.

Abstract: Objective To assess the outcome of extubation in COVID-19 patients and the use of noninvasive ventilation in the weaning process. Methods This retrospective, observational, single-center study was conducted in COVID-19 patients aged 18 years or older who were admitted to an intensive care unit between April 2020 and December 2021, placed under mechanical ventilation for more than 48 hours and progressed to weaning. Early extubation was defined as extubation without a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…More recent literature has shown that patients with COVID-19 once intubated have high rates of extubation failure with low use of prophylactic noninvasive ventilation (NIV). [28] Additional studies have shown that extubation to NIV can decrease the rates of reintubation but without increasing length of stay or mortality. [29] Our study looked at tracheostomies' outcomes for all COVID-19 patients at Mount Sinai Hospital based on the timing of the tracheostomy over a period of 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…More recent literature has shown that patients with COVID-19 once intubated have high rates of extubation failure with low use of prophylactic noninvasive ventilation (NIV). [28] Additional studies have shown that extubation to NIV can decrease the rates of reintubation but without increasing length of stay or mortality. [29] Our study looked at tracheostomies' outcomes for all COVID-19 patients at Mount Sinai Hospital based on the timing of the tracheostomy over a period of 1 year.…”
Section: Discussionmentioning
confidence: 99%